2012
DOI: 10.1038/ajg.2012.284
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Incontinence in the Elderly: FAQ

Abstract: Fecal incontinence (FI) is a common gastrointestinal (GI) complaint in patients aged 65 years and older. This evidence-based review article discusses the epidemiology, pathophysiology, evaluation, and management of FI in the geriatric population. We emphasize aging-related changes leading to and impacting evaluation and treatment of this symptom while incorporating the core geriatric principles of functional status and management aligned with patient preference and goals of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
3
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 93 publications
1
43
3
5
Order By: Relevance
“…From the results of this research, it was observed that almost 43% of the institutionalized elderly presented involuntary losses of feces, a prevalence value that agrees with the ranges presented in literature, which generally vary between 33% and 65% (Saga et al, 2013;Shah et al, 2012;Zarate et al, 2008). However, the severity of the incontinence in this sample was higher, considering that most residents with FI did not present any episodes of continence, with liquid and solid stool losses (Aslan et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…From the results of this research, it was observed that almost 43% of the institutionalized elderly presented involuntary losses of feces, a prevalence value that agrees with the ranges presented in literature, which generally vary between 33% and 65% (Saga et al, 2013;Shah et al, 2012;Zarate et al, 2008). However, the severity of the incontinence in this sample was higher, considering that most residents with FI did not present any episodes of continence, with liquid and solid stool losses (Aslan et al, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, physical inactivity and immobility lost statistical significance when adjusted in the multivariate model. Regarding chronic diseases, it has already been reported that the increase in FI prevalence in the elderly is not explained by the higher presence of comorbidities (Shah et al, 2012). In this study, there were no associations between chronic diseases and FI, and only stroke was present in the multivariate model, as an adjustment variable.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Etiologic factors for intractable diarrhea include diabetes mellitus, multiple sclerosis, scleroderma, and other systemic disorders. 1 Other etiologic factors include infl ammatory bowel diseases, antibiotic use, lactulose, tube feedings, and infectious cases, including Clostridium diffi cile . Fecal incontinence leads to skin breakdown commonly referred to as incontinence-associated dermatitis (IAD).…”
Section: ■ Introductionmentioning
confidence: 99%